Pengujian Kualitas Air Minum Isi Ulang (AMIU) dan Higiene Sanitasi Depot Air Minum Isi Ulang (DAMIU) di Kabupaten Manokwari Provinsi Papua Barat - Rosmawati; Sabariah, Vera; Dwiranti, Febriza; Raharjo, Syafrudin (Program Pascasarjana Universitas Papua, 2026)
ABSTRACT : Refillable Drinking Water (AMIU) is water that has been specially treated through the process of filtration, distillation and irradiation using ultraviolet light. This study aims to determine the quality of refillable drinking water produced by the Refillable Drinking Water Depot (DAMIU) in Manokwari Regency based on the quality standard of the Minister of Health of the Republic of Indonesia No. 2 Tahun 2023. The study was conducted in March-April 2023, and the method used was quantitative descriptive. Refillable drinking water samples were obtained by purposive sampling of 20 samples from 5 District areas in Manokwari Regency. The results of drinking water quality tests for physical, chemical and microbiological parameters were 3 DAMIU water samples from 20 DAMIUs that did not in accordance with the chemical requirements (chromium content 0.06 mg / L and nitrite 3.5 mg/L), and there were 2 DAMIU water samples that did not suit to the microbiological requirements (E.coli 17/100mLto 979 / 100 ml samples and total coliform 17/100ml to 60 / 100ml samples).